Cross-border cooperation: the meaning of cognitive and normative expectations for the emergence of Global research and development cooperation - Thomas Dietz; Holger Nieswandt (Universität Bremen, Collaborative Research Center 597 - Transformations of the State, 2007)
Drawing on Niklas Luhmann's theory of social systems, we analyse the importance of different styles of expectation (cognitive and normative) for global research and development. In our study, we find that contrary to Luhmann's prediction in 1971, the normative expectation style still plays a vital role for the cooperative deals under examination. The second result of our study is that non-state mechanismus such as reputation, resource-dependency and trust are highly important for the stabilization of normative expectations in global business transactions. The role of the state-based legal system is reduced to stabilizing few, albeit crucial, normative expectations.
Keywords: 330; Industrielle Forschung; Forschungskooperation; Multinationales Unternehmen; Erwartungstheorie; Kognition; Systemtheorie; Welt